MANFAAT BIAYA KUALITAS TERHADAP KEUNGGULAN BERSAING PERUSAHAAN - Aprinawati; Asima Br Sianipar; David Lumban Tobing; Wahyu Pradika; Yuninda Febbiola Nst (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Since not every business can produce high-quality products, those that do will have an advantage over their competitors in controlling the market. A corporation needs to be able to do every task more effectively in order to generate high-quality products and services at fair and competitive rates in an effort to boost customer satisfaction if it hopes to succeed globally. Companies require funding in order to determine the degree to which they have applied the functions of their quality control system in order to get the required level of product quality. We refer to these expenses as quality costs. In this instance, quality costs are anticipated to play a part in the company's.